Addition of Intrathecal Morphine for Postoperative Pain Management in Pediatric Spine Surgery: A Meta-analysis. Issue 3 (April 2019) - Musa, Arif; Acosta, Frank L.; Tuchman, Alexander; Movahedi, Rana; Pendi, Kasim; Nassif, Leila; Farhan, Saif Aldeen; Muallem, Emile; Gucev, Gligor
Abstract : Study Design: Meta-analysis. Objective: The objective of this study was to determine whether adjunctive intrathecal morphine (ITM) reduces postoperative analgesic consumption following pediatric spine surgery. Summary of Background Data: Previous studies that have tested supplemental ITM to manage pain after pediatric spine surgery have been limited by small sample sizes. Methods: A comprehensive search of PubMed, Web of Science, Clinicaltrials.gov, and the Cochrane Central Register of Controlled Trials was performed for clinical trials and observational studies. Time to first analgesic demand, postoperative analgesic use, pain scores, and complication data were abstracted from each study. Mean difference (MD) and 95% confidence interval (CI) were used to compare continuous outcomes and odds ratios (OR) and 95% CI were used for dichotomous outcomes. Results: A total of 5 studies, including 3 randomized controlled trials and 2 retrospective chart reviews, containing 636 subjects, were incorporated into meta-analysis. Subjects that were administered ITM in addition to postoperative analgesics (ITM group) were compared with those receiving postoperative analgesics only (control group). In the ITM group, time to first analgesic demand was longer (MD, 8.79; 95% CI, 4.20-13.37; P <0.001), cumulative analgesic consumption was reduced at 24 hours (MD, −0.40; 95% CI, −0.56 to −0.24; P <0.001), and cumulative analgesic consumption was reduced at 48 hours (MD, −0.43; 95% CI, −0.59 to −0.27; P <0.001). Neither postoperative pain scores at 24 hours ( P =0.16) nor 48 hours ( P =0.18) were significantly different between ITM and control groups. Rates of respiratory depression, nausea, vomiting, and pruritus were not different between groups (all P s>0.05). Conclusions: Addition of ITM in pediatric spine surgery produced a potent analgesic effect in the immediate postoperative period. Patients administered ITM did not request opiates as early as control and consumed fewer opiates by the second postoperative day. Furthermore, use of ITM did not increase complications such as respiratory depression, nausea, vomiting, or pruritus.